2015
DOI: 10.1155/2016/1689602
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Attenuates Myocardial Ischemia/Reperfusion Injury by Reducing Oxidative Stress and Inflammation Response: Role of Silent Information Regulator 1

Abstract: Berberine (BBR) exerts potential protective effect against myocardial ischemia/reperfusion (MI/R) injury. Activation of silent information regulator 1 (SIRT1) signaling attenuates MI/R injury by reducing oxidative damage and inflammation response. This study investigated the antioxidative and anti-inflammatory effects of BBR treatment in MI/R condition and elucidated its potential mechanisms. Sprague-Dawley rats were treated with BBR in the absence or presence of the SIRT1 inhibitor sirtinol (Stnl) and then su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 43 publications
4
91
0
Order By: Relevance
“…Myocardial infarct size were measured after 6 h of reperfusion by Evans blue/TTC double-staining technique (Solarbio Technology, Beijing, China) as described previously54. The area at risk (AAR), infarct size (INF) and viable area were assessed digitally using Image-Pro Plus software (Media Cybernetics, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial infarct size were measured after 6 h of reperfusion by Evans blue/TTC double-staining technique (Solarbio Technology, Beijing, China) as described previously54. The area at risk (AAR), infarct size (INF) and viable area were assessed digitally using Image-Pro Plus software (Media Cybernetics, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been reported that continuous intake of more than 800 mg per day may cause liver toxicity in patients (Hu et al, 2018). Finally, the alkaloid polyphenol berberine activates autophagy via SIRT1 and reduces protein acetylation (Shukla et al, 2016), protecting liver function (Sun et al, 2018), exerting neuroprotective effects (Wang et al, 2017), and reducing cardiac damage (Yu et al, 2016) in rodents. Berberine was also shown to extend the lifespan of Drosophila (Navrotskaya et al, 2012).…”
Section: Resveratrol and Other Sirt1 Activatorsmentioning
confidence: 99%
“…Apoptotic cells in 10 fields (randomly chosen) in each group were counted to calculate the apoptotic index: apoptotic index D positive cells/ (positive cells C negative cells) £ 100%. 42…”
Section: Tunel Stainingmentioning
confidence: 99%